Genetic diversity and population structure of naturally rare Calibrachoa species with small distribution in southern Brazil - John, Ana Laura de Wallau; Mäder, Geraldo; Fregonezi, Jeferson N.; Freitas, Loreta B. (Genetics and molecular biology, 2019)
Calibrachoa is a South-American genus comprising 27 species, several considered endemic or rare; few were subjects in genetic studies. We attempted to generate new data about the phylogenetically related and rare species C. eglandulata, C. sendtneriana, C. serrulata, and C. spathulata concerning their genetic diversity and population structure, which, coupled with their known restricted distribution, could help access their conservation status and contribute to the study of the Brazilian biodiversity. We sequenced 88 individuals for plastid intergenic spacers and genotyped 186 individuals for five microsatellite loci. Compared among each other, C. sendtneriana and C. serrulata presented the highest values of genetic diversity [π% (sd) = 0.23 (0.14) and 0.43 (0.25), respectively], followed by C. spathulata [π% (sd) = 0.19 (0.12)] and C. eglandulata [π% (sd) = 0.02 (0.03)]. Population differentiation was evident for these latter species, whereas it was not significant for C. sendtneriana and C. serrulata. Factors such as habitat specificity and fragmentation, pollination syndrome, and life history could explain the observed patterns. Based on the new genetic data and the species' biology, a conservation status was assigned for C. sendtneriana and the status of the other three species was reviewed.